Crafting presence: the American essay and the future of writing studies - Wallack, Nicole B., author; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
Wallack illuminates the most important quality of the essay as a literary form: the writer's 'presence'. She demonstrates how accounting for presence provides a flexible and rigorous heuristic for reading that can help teach students not just writing skills, but writing practices.--Provided by publisher.
The genre of presence -- Historical thinking in essays: crafting presence in the company of ghosts -- Error and illumination: crafting reading presences -- Crafting a self made of images in essay -- Learning the essay.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Essay -- Authorship -- Study and teaching (Higher)